Sintesis Membran Molecularly Imprinted Polymers (MIPs) dan Karakterisasinya sebagai Bahan Penyerap Asam Urat - Atika, Rahma; Ulianas, Alizar (Jurusan Kimia FMIPA UNP, 2019)
MIPs is an polymers that have cavities release the template molecules. The cavity serves to separate the analyte by recognizing target molecules based on their shape, size, structure, physical and chemical properties. MIPs have a high level of sensitivity and selectivity. In the review of this article, it is discussed about membrane synthesis MIPs, the effect of uric acid solution pH and optimizaton time on the adsorption of MIPs. Power capability MIPs adsorption of uric acid was analyzed using FTIR (Fourier Transform Infra Red). Based on article review that MIPs are able to adsorbtion uric acid seen from the peak adsorption of C=O and C-N groups in the area 1673 cm-1 and 1290 cm-1 region which are characteristic of the amides found in MIPs reextraction. Whereas in the extraction MIPs there was no peak adsorption of the C-N group. Peak adsorption this C-N group is only owned by pure uric acid and is not present in MIPs. In addition there is influence significant adsorption of MIPs against uric acid with differences in adsorption time and pH uric acid solution. MIPs can be applied to adsorb uric acid in blood samples.